La questione della temporalità dalla corporeità alla carne - Vanzago, Luca (Scenari, 2024)
This essay discusses the conception of temporality elaborated by Merleau-Ponty in the Phenomenology of Perception, in order to show that this question is central to understanding the entire project configured by Merleau-Ponty in the first phase of his work, i.e. since The Structure of behavior, which represents the necessary complement to correctly understand the theses of the major work. But starting from the results acquired from the investigation, it can be seen how since that work Merleau-Ponty actually laid the foundations for a radicalization of the concept of temporality in the direction of the ontology of later writings, in particular of The Visible and the Invisible, the outcome of which unfortunately was not completed by the author.